Teacher Autonomy Support in Physical Education Classes as a Predictor of Motivation and Concentration in Mexican Students - Maldonado, Erasmo; Zamarripa, Jorge; Ruiz-Juan, Francisco; Pacheco, Rosana; Delgado, Maritza (Frontiers in Psychology, 2019)
There is a strong belief that physical education can affect an individual’s physical activity, healthy habits and behaviors through pleasant, positive and significant exercise experiences, a practical knowledge base, and comprehensive teaching strategies. However, a crucial cognitive aspect for the effective and significant learning of the activities offered in the educational environment is the concentration of students. This study aims to test a hypothetical model based on self-determination theory to assess the degree of support prediction provided by the teacher for student autonomy in the various types of motivation and on student concentration in physical education classes in high schools within the Mexican context and test invariance across gender groups. This study included 859 students between 11 and 16 years from different high schools in the city of San Nicolás de los Garza, Nuevo León (México). The Learning Climate Questionnaire, the Perceived Locus of Causality and the Concentration scale adapted to physical education and translated into Mexican Spanish was used. Results showed good internal consistency for all instruments. Both the measurement model and the structural equation modeling showed satisfactory adjustment indexes. The results revealed that the autonomy support positively predicted autonomous motivation, controlled motivation to a lesser extent, and amotivation negatively. Furthermore, the students’ concentration was highly and positively predicted by autonomous motivation, by controlled motivation to a lesser extent, and by amotivation negatively. The model predicted 39% of variance of autonomous motivation with large effect size (ƒ2 = 0.64), 2% of controlled motivation with small effect size (ƒ2 = 0.02), 8% of amotivation with small effect size (ƒ2 = 0.09), and 49% of concentration with large effect size (ƒ2 = 0.96). Finally, the invariance analysis revealed that the model fit was invariant across gender groups. The results of this study emphasize how important it is for teachers to adopt an interpersonal style of autonomy support to generate a motivational climate that influences the concentration of students. This could contribute to the achievement of the purposes and educational objectives of the physical education class which, in turn, might be conducive to students adopting healthy lifestyles in adolescence and beyond.